LGBTQ+ Fertility in Thailand: A Structural Relations Between Economic Elites, Government, and Civilians - Marenda Athallah Farras Majid (Aimmah: Social Sciences Journal, 2025)
This study analyzes the socio-political and economic frameworks that influence the visibility, advancement, and incorporation of LGBTQ+ communities in Thailand. The qualitative examination of secondary data indicates that Thailand's capitalist change over the last forty years, especially in Bangkok, has facilitated the selective visibility of LGBTQ+ individuals which predominantly rich, urban homosexual men, within consumer-centric paradigms. Institutional support, exemplified by policies such as the Gender Equality Act and the proposed Life Partnership Law, has afforded legal legitimacy; yet, it remains inconsistent and inadequate in practice. Thai government's involvement seems to be more influenced by elite interests and foreign factors than by grassroots lobbying within the country. Civilian actors such as activists, students, and NGOs, have emerged as crucial agents in advocating for reform and promoting inclusive discourse. Nonetheless, class gaps persist in influencing whose opinions are acknowledged and safeguarded. The report asserts that substantial LGBTQ+ inclusion in Thailand must address the intertwined economic and political obstacles, rather than solely commemorate symbolic advancements. This study underscores the pressing necessity for early social awareness in addressing LGBTQ+ that threaten fundamental national values. In the absence of such supervision, these dynamics may become structurally entrenched and affect political authority at the highest echelons.